Determinants Of Electric Smoking Behavior Of State Vocational School Students In Jambi City - Wenty Dameria Purba; M.Ridwan; La Ode Reskiaddin (Jurnal EduHealth, 2024)
E-cigarette use continues to increase globally among adults and adolescents. This situation is increasingly urgent and concerning considering its impact on health. This research was conducted to determine the factors related to e-smoking behavior among State Vocational School students in Jambi City. Method: This research uses a quantitative design with a cross-sectional approach. The population of this study were State Vocational School students in Jambi City with a sample size of 277 respondents. The sampling technique uses non-probability sampling in the form of accidental sampling. The variables in this study are advertising, family economics, and history of conventional cigarettes. Primary data collection was carried out by interviews with questionnaires. Data were analyzed using the chi square test. Results: E-smoking behavior among State Vocational School students in Jambi City was 50.18. There was a relationship between advertising (OR = 3.50; 95% CI = 1.96-6.24), and history of conventional cigarettes (OR = 2.05; 95 % CI=1.30-3.24) with e-smoking behavior. There was no relationship between family economics (OR = 7.78; 95% CI = 4.08-14.83) with e-smoking behavior. Conclusion: Factors related to smoking behavior are the influence of advertising and a history of conventional smoking. Schools can provide regular education and warnings about the dangers of smoking, both electric and conventional, to students and provide motivation about the importance of quitting smoking.